Carbon Nanotubes: A Review on Structure and Their Interaction with Proteins - N. Saifuddin; A. Z. Raziah; A. R. Junizah (Journal of Chemistry)
Carbon nanotubes (CNTs) are allotropes of carbon with a nanostructure that can have a length-to-diameter ratio greater than 1,000,000. Techniques have been developed to produce nanotubes in sizeable quantities, including arc discharge, laser ablation, and chemical vapor deposition. Developments in the past few years have illustrated the potentially revolutionizing impact of nanomaterials, especially in biomedical imaging, drug delivery, biosensing, and the design of functional nanocomposites. Methods to effectively interface proteins with nanomaterials for realizing these applications continue to evolve. The high surface-to-volume ratio offered by nanoparticles resulted in the concentration of the immobilized entity being considerably higher than that afforded by other materials. There has also been an increasing interest in understanding the influence of nanomaterials on the structure and function of proteins. Various immobilization methods have been developed, and in particular, specific attachment of enzymes on carbon nanotubes has been an important focus of attention. With the growing attention paid to cascade enzymatic reaction, it is possible that multienzyme coimmobilization would be one of the next goals in the future. In this paper, we focus on advances in methodology for enzyme immobilization on carbon nanotubes.